Serological Detection of Antibodies to Peste des Petits Ruminants Virus in Large Ruminants - Muhammad Abubakar; Mana Mahapatra; Murali Muniraju; Muhammad Javed Arshed; E H Khan; Ashley C. Banyard; Qurban Ali; Satya Parida (2015)
Peste des petits ruminants (PPR) is an economically important disease of small ruminants with a rapidly expanding geographical distribution. Peste des petits ruminants virus may manifest in a variety of ways with disease ranging from acute to subclinical. We investigated the exposure of large ruminants to PPRV in areas where the virus is endemic in the small ruminant population by assessing the serological status of groups of animals. This study focused on the Punjab province of Pakistan as an area where the virus is endemic and where mixed farming practices occur enabling close interactions between small and large ruminant populations. An overall PPR seropositivity was detected in 10.0% of cattle and 14.16% of buffaloes. Following an assessment of serological profiles in large ruminants within different age groups, a maximum seroprevalence was observed in cattle (17.5%) and buffaloes (22.5%) over 2 years of age indicating the potential utility of sampling large ruminant populations for PPR serosurveillance. The large ruminants sampled between one and two years of age had similar levels of seropositivity within populations with 11.2% and 16.2% of animals being seropositive, respectively. Current PPR vaccination strategies do not enable the differentiation between infected and vaccinated small ruminants, and as such, the serological surveillance of sheep and goats is of little value. When considering eradication programmes for PPRV, this factor is of great significance. However, where large and small ruminants are farmed together, serological surveillance of large ruminants may provide a snapshot of virus infection within populations where mild disease is present or where small ruminants are regularly vaccinated.